Pengenalan Psikologi Anak Dalam Pembentukan Karakter di PAUD Insan Kaamil Teniga Kabupaten Lombok Utara - Prisma Mahendra, Juandra; Musafir, Musafir; Rahayu, Fitriani; Syahnia, Lani (Jurnal Pengabdian Masyarakat Sains Indonesia (Indonesian Journal Of Science Community Services), 2023)
This article discusses the importance of introducing child psychology in character formation in Insan Kaamil Teniga Early Childhood Education (PAUD), North Lombok Regency. This service aims to explore how understanding child psychology can influence teaching methods and social interactions in educational institutions. Using a qualitative approach, data was collected through interviews, observation and documentation studies. The results of the service show that a good understanding of child psychology contributes to the development of positive character in children, as well as improving the quality of education at PAUD Insan Kaamil.